The effect of moisture content to the physical properties of long grain paddy (Oryza sativa) - Muchlisyiyah, Jhauharotul; Shamsudin, Rosnah; Basha, Roseliza Kadir; Shukri, Radhiah; How, Syahmeer (Khon Kaen University,Research and Technology Transfer Affairs Division, 2024)
A new long-grain rice variety known as MR297 has gained popularity in Malaysia. This cultivar is recognized for its high resistance to rust disease. The physical changes in the long grains of MR297 can be influenced by the moisture content of the paddy. This research examined the moisture-dependent physical characteristics of several Malaysian MR297 paddy cultivar samples at different moisture content levels (16.49, 19.81, 25.36, 28.67, and 34.08%; wet basis). The moisture was adjusted by soaking the rice in excess water, after which it was drained and kept overnight in a closed container at room temperature to obtain equilibrium moisture content before analysis. As the moisture content increased, there were significant increases in the length (10.03 to 10.36 mm), width (2.12 to 2.23 mm), thickness (1.86 to 1.98 mm), aspect ratio (0.21 to 0.22), arithmetic mean diameter (4.67 to 4.68 mm), equivalent mean diameter (3.41 to 3.58 mm), geometrical mean diameter (3.41 to 3.57 mm), sphericity (0.34 to 0.36), surface area (34.81 to 38.04 mm2), volume (20.81 to 26.57 mm3) and thousand kernel weight (31.554 to 35.575) (p <0.05). The relationships between the physical characteristics of the MR297 rice cultivars and their moisture content were effectively expressed by linear regression models. The results suggested that increasing the moisture content of grain kernels changes their physical properties. To prevent kernel damage and sustain equipment capacity during processing and handling, changes in physical properties during processing could be considered in equipment design parameters.